2021
DOI: 10.4018/ijhcitp.2021010104
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Employability Skills of Budding IT Professionals in India

Abstract: The purpose of this study is to identify employability skills among aspiring engineering graduates and develop measurement scale to assess their skill sets. This research has been conducted in two phases: Phase 1 covers the scale development process and Phase 2 covers exploratory factor analysis (EFA), confirmatory factor analysis (CFA) and validation. The findings of EFA resulted in ten factors of employability. Subsequently, CFA identified nine different factors: leadership, critical thinking, numeracy, soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Having combined all these standardised questionnaires, data was collected on the seven-point Likert scale which is more accurate and provides an improved reflection of a respondent's accurate assessment. Furthers the insight from literature review and experts' guidance, the questionnaire was found suitable for use in the IT sector (Misra, 2021). Beside this the reliability and validity statistics is represented below in the table 2 and table 3 with elaborations.…”
Section: Tools and Techniquementioning
confidence: 96%
See 2 more Smart Citations
“…Having combined all these standardised questionnaires, data was collected on the seven-point Likert scale which is more accurate and provides an improved reflection of a respondent's accurate assessment. Furthers the insight from literature review and experts' guidance, the questionnaire was found suitable for use in the IT sector (Misra, 2021). Beside this the reliability and validity statistics is represented below in the table 2 and table 3 with elaborations.…”
Section: Tools and Techniquementioning
confidence: 96%
“…This sector is one of the growing sectors in India which accounted for 8% of GDP in the year 2020. IT sector is more employee centric (Khurana & Misra 2021) and has always been considerate about finding the ways to enhance organizational effectiveness. Job satisfaction, organizational commitment and organizational climate are commonly studied variables in this sector, but studies of their role as predictor of organizational effectiveness is limited.…”
Section: Organizational Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the glamorous world, on the other hand, is revealing a distinct picture, where people are increasingly moving towards virtual space for both searching as well as building relationships. The key determinants of this transition are technological advancements, a competitive work place environment, and an active lifestyle (Hu and Kellinger, 2008;Tarafdar, et al, 2020;Khurana and Misra, 2021). People are becoming more task-driven and output-oriented to gain success in their professional lives by compromising their personal relationships.…”
Section: Introductionmentioning
confidence: 99%